Investigation of magneto-structural phase transition in FeRh by reflectivity and transmittance measurements in visible and near-infrared spectral region - Saidl, V.; Brajer, M.; Horák, L.; Reichlová, H.; Výborný, K.; Veis, M.; Janda, T.; Trojánek, F.; Marysko, M.; Fina, I.; Marti, X.; Jungwirth, T.; et al. (IOP Publishing, 2016)
Magneto-structural phase transition in FeRh epitaxial layers was studied optically. It is shown that the transition between the low-temperature antiferromagnetic phase and the high-temperature ferromagnetic phase is accompanied by a rather large change of the optical response in the visible and near-infrared spectral ranges. This change is consistent with ab initio calculations of reflectivity and transmittance. Phase transition temperatures in a series of FeRh films with thicknesses ranging from 6 to 100 nm is measured thereby demonstrating the utility of the method to quickly characterise samples. Spatially resolved imaging of their magnetic properties with a micrometer resolution shows that the phase transition occurs at different temperatures in different parts of the sample.